Social support for de-carbonizing the energy system: The role of expressive partisanship. Issue 109 (July 2020) - Mayer, Adam
Highlights: Climate change and climate change policies are highly partisan in the U.S. The effect of expressive partisanship on climate change attitudes is unknown. Identity-based vs. instrumental accounts of partisan identity. Results are consistent with an identity-based perspective on partisanship. Abstract: The partisan divide on climate policy in the United States is well-documented. Decarbonizing the energy system is key to addressing climate change, and social support for many energy policies is not as starkly partisan as the question of the existence of climate change. In this analysis, we blend insights from social psychology and political science that suggest that partisanship is a social identity with varying salience across individuals. We integrate the concept of expressive partisanship with research on social support for energy policy by arguing that there are potentially two types of expressive partisans—ideological and identitarian expressive. Using data from the Climate Change in the American Mind study, our results imply that partisan polarization on energy and climate policy is driven by identitarian expressiveness, rather than deep ideological differences between liberals and conservative, or Democrats and Republicans.